Caribbean Report 23-04-1997 - Orr, Carol (anchor); Maraj, Ralph (interviewee); Bannister, Piers (interviewee); Richards, Ken (correspondent); Madix, Winfred (interviewee); Smith, Clifford (correspondent); Goffe, Leslie (correspondent); Fraser, Tony (correspondent) (The British Broadcasting Corporation, 1997)
Trinidad and Tobago’s Foreign Minister says his government will not tolerate Venezuela’s continuing violation of its territorial sovereignty. Next, in French Guiana the Pro-Independence Movement rejected claims by the authorities that the organisation was trying to destabilise the country. Next, in Jamaica the Ministry of National Security and Justice has refuted the claims of allegations of brutality against several death row prisoners who attempted a breakout from the St Catherine’s District Prison. However, Amnesty International remains dissatisfied with the assertion that no abuse of human rights took place. Hospital authorities say that four prisoners were treated for injuries. Next, the Joint Council of Ministers of the European Union and the ACP countries are meeting tomorrow in Luxembourg. On the agenda is the approval of partial membership for South Africa within the Lome Convention as well as subjects of special Caribbean interest are expected to come up especially bananas and rum. In the final segment, the United States social security administration has warned that it is going to clamp down on elderly immigrants, many of them from the Caribbean who illegally collect US benefits.
1. Headlines (00:00-00:40)
2. Trinidad and Tobago issues fierce warnings to Venezuelan Coast Guard abducting fishermen in the twin island's territorial waters. Ralph Maraj, Foreign Minister of Trinidad and Tobago is interviewed (00:41-02:35)
3. Violence in French Guiana. General Secretary of the Pro-independence Movement is interviewed (02:36-05:47)
4. Jamaica's National Security Minister denies prison brutality of inmates but a hospital confirms several were treated for injuries. Piers Bannister of Amnesty International is interviewed and Ken Richards reports (05:48-10:51)
Keywords: Trinidad and Tobago -- Foreign relations.; Pro-independence movement -- French Guiana.; Protest -- French Guiana.; Spanish Town District Prison -- Jamaica.; ACP countries.; Joint Council of Ministers -- European Union.; Social security -- United States.